2014
DOI: 10.5005/jp-journals-10015-1278
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a New Generation Anticavity Mouthwash on Streptococcus mutans and Lactobacillus acidophilus Count: A Microbiological Study

Abstract: Background Dental caries is one of the most widespread disease. CariFree CTx4 treatment rinse mouthwash is designed to treat the cavity-causing plaque biofilm, reduce the overpo pulation of cavity-causing bacteria, and neutralize decaycausing acids with patent-pending pH + technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The comparison of antibacterial effect of 0.2% chlorohexidine, 0.05% sodium fluoride mouthwash and 2% povidone iodine mouthwash against S.mutans was previously reported and the authors concluded that 0.2% Chlorohexidine showed the maximum antibacterial effect on S. mutans which was consistent with our study result [17].…”
Section: Discussionsupporting
confidence: 92%
“…The comparison of antibacterial effect of 0.2% chlorohexidine, 0.05% sodium fluoride mouthwash and 2% povidone iodine mouthwash against S.mutans was previously reported and the authors concluded that 0.2% Chlorohexidine showed the maximum antibacterial effect on S. mutans which was consistent with our study result [17].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, another in vitro study also revealed similar antibacterial and antibiofilm activities of CEO, with fewer adverse effects than CHX against Streptococcus mutans (S. mutans) and Streptococcus pyogenes [26]. Other studies tested the antibacterial effect of fennel seed methanolic extract against the cariogenic bacteria S. mutans, compared it with CHX 0.2%, and found that CHX was more effective and produced a more significant inhibition zone [27,28]. Furthermore, other researchers found that chewing the seeds for five minutes showed a rise in salivary pH that can prevent demineralization and have an anti-cariogenic property [29].…”
Section: Discussionsupporting
confidence: 90%
“…Targeting Streptococcus mutans forms the most important measure for the prevention of dental caries. [4] Current methods of caries management are limited to traditional preventive approaches in combination with restorative treatments. These methods have proved inadequate to control the disease.…”
Section: Introductionmentioning
confidence: 99%